Metodologia para alocação ótima de para-raios em linhas de transmissão objetivando a melhoria do desempenho frente às descargas atmosféricas - Matheus Christino Marzochi (2022)
The direct incidence of atmospheric discharges on overhead transmission lines (OHTLs) is one of the main obstacles to the continuous supply of electricity. A common practice to mitigate the effects of lightning in OHTLs is the installation of overhead ground wires (OHGWs). However, even an OHTL protected by OHGW can present a high number of outages. In this context, seeking to improve the performance of OHTLs, one of the main alternatives is the use of transmission line surge arresters (TLSAs). However, it is important to identify the locations where such devices must be installed to avoid excessive expenditure of financial resources. Therefore, in order to meet the outages limits defined by regulatory agencies and taking into account the financial aspect by minimizing the amount of TLSAs used, this work proposes a methodology for the optimal positioning of TLSAs in OHTLs. This methodology is based on the combination of an optimization algorithm - inspired by General Variable Neighbourhood Search and Genetic Algorithm - with the ATP (Alternative Transient Program). The line performance calculation is made considering the transfer effect of the atmospheric surge due to arresters operation. This transfer mechanism that can lead adjacent towers to flashover is rarely mentioned in the literature. In order to analyze the behavior of the proposed approach, experiments are carried out to optimize the positioning of TLSAs in multiple OHTLs. To validate the developed procedure, the results obtained are compared with others that are provided by coupling a Genetic Algorithm with ATP, and with the results achieved by coupling a General Variable Neighbourhood Search algorithm with ATP. They are also compared to classical methods for the positioning of TLSAs. It is possible to conclude that aspects such as the atmospheric surge transfer effect and favoring the positioning of lightning arresters in the lowest phase(s) should be taken into account in studies for the optimal placement of TLSAs in OHTLs.